2020
DOI: 10.1038/s41467-020-16528-7
|View full text |Cite
|
Sign up to set email alerts
|

In situ evidence of thermally induced rock breakdown widespread on Bennu’s surface

Abstract: Rock breakdown due to diurnal thermal cycling has been hypothesized to drive boulder degradation and regolith production on airless bodies. Numerous studies have invoked its importance in driving landscape evolution, yet morphological features produced by thermal fracture processes have never been definitively observed on an airless body, or any surface where other weathering mechanisms may be ruled out. The Origins, Spectral Interpretation, Resource Identification, and Security-Regolith Explorer (OSIRIS-REx) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 64 publications
10
82
0
Order By: Relevance
“…Independent modelling reached similar conclusions, namely that thermally driven stresses lead to cracking of asteroid surface rocks (Molaro Byrne & Le 2017). In addition, OSIRS-REx Polycam observations, at a spatial resolution of some cm, show that several boulders on the surface of Bennu display fractures and morphologies compatible with an exfoliation process (Molaro et al 2020). The same authors perform a thermo-elastical modelling of the observed boulders, which indicate that the aforementioned features are consistent with the result of releasing stresses generated by temperature cycling.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Independent modelling reached similar conclusions, namely that thermally driven stresses lead to cracking of asteroid surface rocks (Molaro Byrne & Le 2017). In addition, OSIRS-REx Polycam observations, at a spatial resolution of some cm, show that several boulders on the surface of Bennu display fractures and morphologies compatible with an exfoliation process (Molaro et al 2020). The same authors perform a thermo-elastical modelling of the observed boulders, which indicate that the aforementioned features are consistent with the result of releasing stresses generated by temperature cycling.…”
Section: Introductionmentioning
confidence: 60%
“…Boulders with sizes up to several meters dominate areas where fine regolith is apparently lacking (Tsuchiyama et al 2008). The recent observations obtained by NASA's OSIRS-REx and JAXA's Hayabusa2 missions of near-Earth asteroids (101 955) Bennu and (162 173) Ryugu challenged the paradigm that fine regolith is in general present on asteroids: in situ images reveal rugged surfaces almost entirely dominated by boulders (Walsh et al 2019;Watanabe et al 2019;Molaro et al 2020), except in some specific places, such as the sampling site candidates of OSIRIS-REx on Bennu.…”
Section: Introductionmentioning
confidence: 99%
“…Boulders with longer exposure ages are likely to have undergone more cumulative weathering due to processes such as meteoroid bombardment ( 57 , 58 ) and thermal fatigue from temperature cycling ( 59 , 60 ). The inferred strength difference between the low- and high-reflectance boulders suggests that these two boulder types may respond differently to these two weathering mechanisms, which could lead to changes in their relative size frequency distribution over time.…”
Section: Resultsmentioning
confidence: 99%
“…An example may be electrostatic lofting, the amount of which is dependent on cohesion and large electrostatic forces driven by photoemission or secondary electron emission [Hartzell, 2019;Hartzell et al, 2020;Wang et al, 2016;Zimmerman et al, 2016]. Micrometeoroid impacts [e.g., Sugita et al, 2019;Walsh et al, 2019] and thermal cracking [e.g., Molaro et al, 2015Molaro et al, , 2017Molaro et al, , 2020Hazeli et al, 2018] may also result in small particle transportation.…”
Section: Insights Into Reshaping and Top Shapes' Interiors From Surfamentioning
confidence: 99%